Sistem Pewarisan Musik Gandang Sarunai Di Nagari Luak Kapau Kecamatan Alam Pauh Duo Kabupaten Solok Selatan - Mei Hanum Sahef; Marzam Marzam; Erfan Erfan (SENDRATASIK UNP, 2020)
This research aims to describe the Gandang Sarunai music inheritance system in the community of Nagari Luak Kapau, Alam Pauh Duo, Solok Selatan Regency. This research is qualitative research which aims to get things related to the topic. The data related to the topic were collected through literature study, observation, interview, and documentation technique.The results show that the Gandang Sarunai music inheritance system in Nagari Luak Kapau was inherited by using an open system. This inheritance is done in colleges or studios. The heirs must be the ones who have desire, talent, and interest to learn the music of Gandang Sarunai. This open inheritance system in Nagari Luak Kapau also uses several requirements so that the heirs are able to learn and inherit traditional music from the Gandang Sarunai. In addition, the Inheritance System of traditional music gandang sarunai in Nagari Luak Kapau, Pauh Duo district, Solok Selatan Regency, was inherited through enculturation. It is where humans are considered as beings that have logical reasoning, have the power of reflection and intelligence, as well as learn to understand and adapt the mindset, knowledge, and culture of another group of humans.